EFEKTIVITAS MODEL PROBLEM POSING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI SMK SWASTA TERUNA PADANGSIDIMPUAN - Henni Paujiah Tanjung; Nunik Ardiana; sinar Depi Harahap (JURNAL MathEdu (Mathematic Education Journal), 2020)
The aim of this study is to describe the effectiveness of using problem posing learning model on students’ mathematical problem solving ability on the topic of angle size (degrees and radians) at the tenth grade students of SMA Negeri 1 Angkola Barat. The research was conducted by applying experimental method (one group pretest post test design) with 23 students as the sample and they were taken by using cluster random sampling technique from 214 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using problem posing learning model was 3.66 (very good category) and (b) the average of students’ angle size achievement before using problem posing learning model was 64.34 (enough category) and after using problem posing learning model was 92.91 ( very good category). Furthermore, based on inferential statistic by using pair sample ttest, (SPSS version 16), the result showed the significant value was less than 0.05 (0.000<0.05). It means, problem posing learning model was effective on students’ mathematical problem solving ability on the topic of angle size (degrees and radians) at the tenth grade students of SMA Negeri 1 Angkola Barat.